If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3 = 7x + -11 Reorder the terms: -3 + 10x = 7x + -11 Reorder the terms: -3 + 10x = -11 + 7x Solving -3 + 10x = -11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -3 + 10x + -7x = -11 + 7x + -7x Combine like terms: 10x + -7x = 3x -3 + 3x = -11 + 7x + -7x Combine like terms: 7x + -7x = 0 -3 + 3x = -11 + 0 -3 + 3x = -11 Add '3' to each side of the equation. -3 + 3 + 3x = -11 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -11 + 3 3x = -11 + 3 Combine like terms: -11 + 3 = -8 3x = -8 Divide each side by '3'. x = -2.666666667 Simplifying x = -2.666666667
| 10/2= | | 13=-7p-6p | | a^2-9=40 | | x/5=6/2 | | 5x+11=3+8x-7 | | x-11=-7 | | 18-(x+6)=6x-2 | | 5x^3+15x^2+3x+9=0 | | -11=y-(-35) | | 12=-6-n | | 20*/*2= | | -2x=-24+4x | | 5(3-2x)-2(3x+7)=3(4-5x) | | 20*2= | | 5m-8m=3m+8 | | 20/2= | | 6-6x-3=-33+4x-14 | | 3y(y)=75 | | 20*/2= | | 10+3x=2x-15 | | 2x+y=195 | | 4(x+5)+8=3x-5 | | 3(1-2x)+17=4(x+5) | | 2h+3r=9 | | 10x^2-101x+10=0 | | f(x)=3x^3-7x^2+12x-28 | | 10*=2 | | 24x-7-17x+4=22x-9-15x+13 | | 9x-5=-68 | | 42=-6(2y-3) | | x^2-x+5= | | 3x+6x=117 |